The effect of the feminist movement on painting and sculpture in Europe and America after 1945 - Brooks, Jennifer (Rhodes University, Faculty of Humanities, Department of Fine Art, 1983)
My investigation of women artists and their status in society today as a result of the feminist movement, revealed issues which, I felt, were multifaceted. This necessitated an exploration of many aspects in order to arrive at a fairly satisfactory conclusion as to whether the revolt and the aggression on the part of the feminists had borne any fruit, either generally in everyday life, or artistically. It has proved most stimulating and informative. I think that the need to assess oneself as a woman, working within a male-dominated creative environment is a very necessary process and one which has been most beneficial to me. The subsequent research revealed that a radical, thematic change had occured within the feminist movement at the start of the Eighties; a fact of which, till recently, I was largely unaware. What I discovered was that the militant, feminist approach of the Sixties and Seventies had given way to a more realistic involvement brought on partly by the economic recession and the effects as well of earlier feminist movements, leading to a relaxation on the part of the younger generation. The Violence had faded. Hard times curbed the excesses of the movement and took it along the road to practicality. Dovetailed to this and seeming to run concurrently was the phenomenon of the demise of the Modern Art Movement. These changes described were not only artistic and feminist, but cut right across the board. involving all facets of life. To take one as an example. the political with conservatism reinstating itself in America not merely as an alternative but as a worthwhile direction in itself. Other issues included the sociological, historical, biological, and cultural; all closely interwoven and therefore requiring some generalisations at times. Previous to becoming involved with my topic, I had been reacting to pre-conceived ideas laid on me as a student in the Sixties and Seventies - a militant, aggressive approach acquired as a protective shield, to deal with the masculine environment which denigrated in varying degrees mine and fellow female artists work, sometimes overtly, sometimes subconsciously. This discrimination, is usually denied as ever having existed by the men involved. It shows a lack of awareness of what, we, as female art students, were subjected to. This is one of the main reasons why I undertook this subject; partly out of interest and perhaps partly as some sort of catharsis.
Keywords: Painting, American -- 20th century; Painting, European -- 20th century; Sculpture, European -- 20th century; Sculpture, American -- 20th century; Feminism and art -- United States; Feminism and art -- Europe